(untitled) (Journal of Science and Technology, 2016)
The principles of phase-transfer catalysis was applied for the synthesis of some Gamma-piperazinyl propanols of general formula 1, which were synthesized for the purpose of studying the influence of esterification on their spasmolytic activity. It was found out that, esters of this type can be obtained in very good yields, utilizing the solid-liquid phase-transfer catalyzed (PTC) conditions and not the liquid-liquid PTC conditions. The method and conditions for their successful syntheses are described in this paper.